The antimicrobial activity of plants in the vicinity of a geothermal area in Perak, Malaysia - Mhd Bakri Yuhanis, Syed Abd Azizz Saripah Salbiah, Abdul Talib Munirah, Mohamed Fatimah, (N/A, 2017)
The antimicrobial activity of plants in the vicinity of a geothermal area in Perak, Malaysia by Mhd Bakri Yuhanis, Syed Abd Azizz Saripah Salbiah, Abdul Talib Munirah, Mohamed Fatimah,